2013
DOI: 10.1002/mame.201200405
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Bio‐Based Epoxy Prepolymer Structure on Network Properties

Abstract: International audienceThree different bio-based epoxy prepolymers are studied: one that is synthesized from isosorbide and two that are commercial prepolymers derived from sorbitol and cardanol. The chemical structures are analyzed by SEC, ESI-TOF MS, and FTIR analyses. The bio-based prepolymers exhibit different structures, either aromatic with long aliphatic chains for the epoxy prepolymer derived from cardanol (DGECAR), with high functionality for the sorbitol polyglycidyl ether (SPGE) or a short and cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
1
21
1
Order By: Relevance
“…Experimental results concerning the value of Mc = 140-150 g · mol − 1 are slightly lower than the theoretical values of 210 g · mol − 1 . It has been previously reported that when the values of ν are higher than 5, the experimental values of Mc are always lower than the theoretical ones [18,27]. Consequently, these differences can be explained by the high values of crosslinking density observed (ν = 9.1), which confirm the strong reticulation of the networks.…”
Section: Preparation and Characterization Of Epoxy Networkcontrasting
confidence: 37%
“…Experimental results concerning the value of Mc = 140-150 g · mol − 1 are slightly lower than the theoretical values of 210 g · mol − 1 . It has been previously reported that when the values of ν are higher than 5, the experimental values of Mc are always lower than the theoretical ones [18,27]. Consequently, these differences can be explained by the high values of crosslinking density observed (ν = 9.1), which confirm the strong reticulation of the networks.…”
Section: Preparation and Characterization Of Epoxy Networkcontrasting
confidence: 37%
“…With such characteristics, ISB has been used to synthesize various polyesters, [20][21][22][23][24][25][26][27] epoxy adhesives, [28][29][30] polyurethanes, [31][32][33][34] polycarbonates [35][36][37][38] and medicines. It is one of the promising biomass monomers derived from glucose and it has a diol structure suitable for conden-sation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Its viscosity at 25 °C is 9000 mPa s and the equivalent epoxy weight (EEW) is 184 g eq −1 . SPGE was obtained from Nagase Chemtex with the reference Denacol EX‐622; its EEW is 181 g eq −1 , its viscosity at 25 °C is 11 800 mPa s. This grade was selected following previous studies which showed that this monomer led to more hydrophobic networks . A biobased phenalkamine curing agent derived from cardanol, with the reference NX5619 was supplied by Cardolite.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, two biobased epoxy formulations were selected, one formulated from a biobased DGEBA and PhA, the other from SPGE and the same PhA. Indeed our previous work on the characterization of networks based on sorbitol polyglycidyl ether (SPGE), led us think that this epoxy prepolymer may have potential for the preparation of biobased composites . The present study involves the in‐depth characterization of the monomer structures, the kinetics of the crosslinking reaction, and the characterization of the networks in terms of their thermomechanical properties and hygrothermal ageing.…”
Section: Introductionmentioning
confidence: 99%